Development of dynamic simulator of alkaline water electrolyzer for optimizing renewable energy systems. Issue 1 (1st January 2018) - Kojima, H.; Matsuda, T.; Matsumoto, H.; Tsujimura, T.
Abstract: In order to analyse dynamic behaviours of hydrogen production by alkaline water electrolysis against fluctuating electric power, we developed a large-scale electrolyzer simulator. The measurement data of a 150-kW alkaline water electrolyzer were used in the development of the simulator model. In this study, first, model constants relevant to heat balance in the system were determined based on experimental data obtained by the operation of a 150-kW electrolyzer, in order to simulate the hydrogen generation process over an extensive duration. The results showed that the model can predict the temperature over a period of 24 h. Next, the prediction of temperature and efficiency for different scales of electrolyzers was conducted using the developed simulator to assess the behaviour of various large-scale electrolyzers in practical use. In a large-scale electrolyzer, temperature change due to heat transfer to ambient air reduces; thus, such electrolyzers have an advantage in terms of energy-conversion efficiency. Furthermore, the performance of one large electrolyzer (5 MW) and two small electrolyzers (1 MW each) was predicted and compared. The large electrolyzer had an advantage after its temperature increased because the moderate electrolyzer temperature and low current density could be achieved concurrently owing to a slower cooling speed.